The Haves and the Have-Nots in Latin America in the 20th Century - Pablo Astorga Junquera (Revista de Economía Mundial, 2016)
This paper offers for the first time income shares of the top 10% and the bottom 40% of the labour force for Argentina, Brazil, Chile, Colombia, Mexico and Venezuela in the period 1900-2011. The main findings are: i) over this period the top 10% share is, on average, 51.3% and the bottom 40% share 13.2%; ii) in the last thirty years the gap between both tails widened (54.6% vs. 11.9%), despite narrowing inequality in the 2000s; iii) there is no inequality levelling in the middle decades of the last century as experienced in the rich economies. This new long-term evidence confirms that the recent shared decline in inequality has no precedent in the 20th century; but it also shows that, as in the past, high concentration at the top 10% and a relatively low-income share of the bottom 40% continues to be the region’s inequality trademark.